Religiosity and Resilience in Students of the Faculty of Catholic Religious Education - Ronika Tindaon; Kartika Nur Fathiyah; Yohanes Engelbertus Paji (Journal of Educational, Health and Community Psychology, 2024)
The purpose of this study was to determine the effect of religiosity on resilience in college students. This study used a quantitative approach with a correlational research type with a population of 237 pastoral high school students. The sampling technique used was simple random sampling of 108 people. Data collection used a resilience scale with The 14-Item Resilience Scale (RS-14) and a religiosity scale with The Centrality of Religiosity Scale (CRS). The results found that there was a significant influence between religiosity on resilience in college students, with an effective contribution of 64%. Based on the categorization results, the majority of subjects in this study have resilience and religiosity in the moderate category.